1999
DOI: 10.1002/aic.690450916
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst attrition in fluidized‐bed systems

Abstract: Catalyst attrition has often been a major obstacle in the de®elopment of new fluidized-bed processes and it is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 10 publications
2
59
0
Order By: Relevance
“…For operating parameters, see Table 1 a bubbling bed 18,19 . Matsen 20 reported that laboratory-and pilot-scale equipment usually show slug-flow behaviour, whereas large fluidized beds are generally not in slug flow.…”
Section: Resultsmentioning
confidence: 99%
“…For operating parameters, see Table 1 a bubbling bed 18,19 . Matsen 20 reported that laboratory-and pilot-scale equipment usually show slug-flow behaviour, whereas large fluidized beds are generally not in slug flow.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of coarse material would only be achieved through correct cyclone operations, but as the gas flow rate is actually decreasing during this stage (Fig 6), cyclone efficiencies should be dropping. The increase in fines would be due to attrition, with the products being lost from the system as they are formed [14,15]. As the FCCU was utilising e-cat during start up, which should be stronger than fresh catalyst, these excessive attrition rates can not be fully explained.…”
Section: Second Stagementioning
confidence: 98%
“…From the literature [14,15], it is commonly accepted that the fine fractions are generated through attrition of larger particles. This theory is supported in the initial sample, as a large amount of coarse material is accompanied by fine material, although there is little of this material in the e-cat.…”
Section: Initial Stagementioning
confidence: 99%
“…C j , K b * and C c are particle attrition constants for the jet region, bubbling attrition and cyclone attrition, respectively. The values for these constants were sourced from work by Werther and Reppenhagen [9], since the test material used in the development of their equation, Eq. (1), was also FCC catalyst.…”
Section: Development Of the Modelmentioning
confidence: 99%
“…The original model was expanded to take into account the feedback of collected catalyst from the cyclone into the bed, as well as the addition of an attrition term to more realistically predict emission rates. The attrition terms used in the model were developed by Werther and Rappenhagen [9], Eq. (1):…”
Section: Development Of the Modelmentioning
confidence: 99%